A cluster level study for the identification of the disparities in birth intervals between rural and urban areas of Bangladesh - Farzana Afroz; Fatima Tuz Zahura; Shahnaz Nilima; Sabina Akter (PLoS ONE, 2026)
Like most developing countries, it is pivotal to identify factors associated with birth intervals in Bangladesh for intervening programs to reduce maternal and under-five children deaths. In this study, an attempt has been made to examine the socioeconomic and demographic factors that influence birth intervals in rural and urban Bangladesh. For this purpose, the secondary data extracted from Bangladesh Demographic and Health Survey (BDHS), 2017−18 and 2022 have been utilized where a two-stage stratified sampling technique is used for data collection. The sample has been considered based on the information available on the birth interval for the last child of mothers. We have applied the Product-Limit approach, Log-rank test and the popular semi parametric frailty regression model that takes into account the possible correlation among observations from the same cluster. Slight disparity has been observed in the median birth intervals between urban (64 months, 2017−18; 67 months, 2022) and rural mothers (60 months, 2017−18; 63 months, 2022). In both datasets, age at marriage, women’s decision making autonomy, and division have been emerged as significant determinants of the birth intervals in rural and urban Bangladesh. In the 2017−18 data, the effect of partner’s education is limited to urban areas, while religion shows significance only in rural areas. Meanwhile, in the 2022 data, the wealth index and spousal age difference become significant only in rural areas. It is recommended that the government invest in programs to enhance women’s autonomy, since women’s greater autonomy significantly delays subsequent births in both rural and urban areas. According to the most recent 2022 data, rural women from middle class and rich families have significantly longer birth intervals compared to the poor families, hence promotion of family planning counseling should be more strongly promoted to them. In addition, analysis using 2022 data reveals that in rural areas, birth intervals initially shorten as the spousal age difference increases, then subsequently lengthen after a certain threshold; therefore, family planning initiatives in this area should incorporate guidance on selecting a proper age gap at marriage, which might contribute to longer birth intervals.